Small Duplication of HPRT 1 Gene May Be Causative For Lesh-Nyhan Disease in Iranian Patients - BOROUJERDI, Razieh; SHARIATI, Mohsen; NADDAFNIA, Hosein; REZAEI*, Hojatolah (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Boroujerdi R, Shariati M, Naddafnia H, Rezaei H. Small Duplication of HPRT 1 Gene May Be Causative For Lesh- Nyhan Disease in Iranian Patients. Iran J Child Neurol. 2015 Winter;9(1):103-106. Abstract Deficiency of hypoxanthine-guanine phosphoribosyltransferase (HGPRT) is a rare inborn error of purine metabolism and is characterized by uric acid overproduction along with a variety of neurological manifestations that depend on a degree of the enzymatic deficiency. Inheritance of HPRT deficiency is X-linked recessive; thus, males are generally more affected and heterozygous females are carriers (usually asymptomatic). Human HPRT is encoded by a single structural gene on the long arm of the X chromosome at Xq26. More than 300 mutations in the HPRT1 gene have been detected. Diagnosis can be based on clinical and biochemical findings as well as enzymatic and molecular testing. Molecular diagnosis is the best way as it allows for faster and more accurate carrier and prenatal diagnosis. In this report, a new small duplication in the HPRT1 gene was found by sequencing, which has yet to be reported. References Fu R, Jinnah HA. Genotype-Phenotype Correlations in Lesch-Nyhan Disease Moving Beyond The Gene. Journal of Biological Chemistry. 2012; 287(5):2997- 3008. Fontenelle LJ, Henderson JF. An enzymatic basis for the inability of erythrocytes to synthesize purine ribonucleotides de novo. Biochim Biophys Acta. 1969 Feb 18; 177(1):175-6. PubMed PMID: 5781193. Kelley WN, Wyngaardcn JB. Clinical syndromes associated with hypoxanthine guanine Phosphoribosyl transferase deficiency. In: J. B. Stanbury, J. B. Wyngaarden, D. S. Frederickson, J. L. Goldstein, M. S. Brown, editors. The Metabolic Basis of Inherited Disease. 5 ed. New York: McGraw Hill; 1983. p. 1115-43. Lesch M, Nyhan WL. A Familial Disorder of Uric Acid Metabolism and Central Nervous System Function. Am J Med. 1964 Apr; 36:561-70. PubMed PMID: 14142409. Christie R, Bay C, Kaufman IA, Bakay B, Borden M, Nyhan WL. Lesch-Nyhan disease: clinical experience with nineteen patients. Dev Med Child Neurol. 1982 Jun; 24(3):293-306. PubMed PMID: 7095300. Neychev VK, Jinnah HA. Sudden death in Lesch-Nyhan disease. Dev Med Child Neurol. 2006 Nov; 48(11):923- 6. PubMed PMID: 17044962. PubMed Central PMCID: 3507438. Torres RJ, Puig JG. Hypoxanthine - guanine phosphoribosyltransferase (HPRT) deficiency: Lesch- Nyhan syndrome. Orphanet J Rare Dis. 2007; 2:48.PubMed PMID: 18067674. PubMed Central PMCID: 2234399. Finette BA, Kendall H, Vacek PM. Mutational spectral analysis at the HPRT locus in healthy children. Mutat Res. 2002 Aug 29; 505(1-2):27-41. PubMed PMID: 12175903. Patel PI, Framson PE, Caskey CT, Chinault AC. Fine structure of the human hypoxanthine phosphoribosyltransferase gene. Mol Cell Biol. 1986 Feb; 6(2):393-403. PubMed PMID: 3023844. PubMed Central PMCID: 367528. Edwards A, Voss H, Rice P, Civitello A, Stegemann J, Schwager C, et al. Automated DNA Sequencing of the human HPRT locus. Genomics. 1990 Apr; 6(4):593-608. PubMed PMID: 2341149. Jinnah HA, De Gregorio L, Harris JC, Nyhan WL, O’Neill JP. The spectrum of inherited mutations causing HPRT deficiency: 75 new cases and a review of 196 previously reported cases. Mutat Res. 2000 Oct; 463(3):309-26. PubMed PMID: 11018746. Epub 2000/10/06. eng. Jinnah HA, Harris JC, Nyhan WL, O’Neill JP. The spectrum of mutations causing HPRT deficiency: an update. Nucleosides Nucleotides Nucleic Acids. 2004 Oct; 23(8-9):1153-60. PubMed PMID: 15571220. Epub 2004/12/02. eng. Bouwens-Rombouts AG, van den Boogaard MJ, Puig JG, Mateos FA, Hennekam RC, Tilanus MG. Identification of two new nucleotide mutations (HPRTUtrecht and HPRTMadrid) in exon 3 of the human hypoxanthine-guanine phosphoribosyltransferase (HPRT) gene. Human genetics. 1993 Jun; 91(5):451-4. PubMed PMID: 8314557. Lovett ST, Drapkin PT, Sutera VA, Jr., Gluckman- Peskind TJ. A sister-strand exchange mechanism for recA-independent deletion of repeated DNA sequences in Escherichia coli. Genetics. 1993 Nov; 135(3):631- 42. PubMed PMID: 8293969. PubMed Central PMCID: 1205708. Hartl L.D, Ruvolo M. Genetic Analysis of Genes and Genomes. Burlington: Jones & Bartlett Learning; 2012. p. 529. McKeran RO, Andrews TM, Howell A, Gibbs DA, Chinn S, Watts WE. The diagnosis of the carrier state for the Lesch–Nyhan syndrome. Q J Med. 1975 Apr; 44(174):189-205. PubMed PMID: 1178810. O’Neill JP. Mutation carrier testing in Lesch-Nyhan syndrome families: HPRT mutant frequency and mutation analysis with peripheral blood T lymphocytes. Genet Test. 2004 Spring; 8(1):51-64. PubMed PMID: 15140374. Torres RJ, Buno A, Mateos FA, Puig JG. Carrier state in HGPRT deficiency. A study in 14 Spanish families. Adv Exp Med Biol. 1998; 431:197-200. PubMed PMID: 9598058. Kleijer WJ, Van Den Berg P, Los FJ. Prenatal diagnosis of Lesch-Nyhan disease. Prenat Diagn. 2004 Aug; 24(8):658-9; author reply 9. PubMed PMID: 15305358. Graham GW, Aitken DA, Connor JM. Prenatal diagnosis by enzyme analysis in 15 pregnancies at risk for the Lesch- Nyhan syndrome. Prenat Diagn. 1996 Jul; 16(7):647-51. PubMed PMID: 8843475. Gibbs RA, Nguyen PN, McBride LJ, Koepf SM, Caskey CT. Identification of mutations leading to the Lesch- Nyhan syndrome by automated direct DNA sequencing of in vitro amplified cDNA. Proceedings of the National Academy of Sciences of the United States of America. 1989 Mar; 86(6):1919-PubMed PMID: 2928313. PubMed Central PMCID: 286816. Mak BS, Chi CS, Tsai CR, Lee WJ, Lin HY. New mutations of the HPRT gene in Lesch-Nyhan syndrome. Pediatric neurology. 2000 Oct; 23(4):332-5. PubMed PMID: 11068166.